Testes e estimações dos modelos de consumo agregado - Monteiro, Marcel Stanlei (2019)
The content of this thesis refers to the tests and estimations of consumption models through the use of utility functions of the CRRA type and External Habit. In the first chapter, the tests occurred with the use of stochastic factor discount models for Brazilian data. In the second, the estimations occurred with the use of common factor portfolios constructed from a large set of asset return data from the US stock market, in order to bring new evidence about the behavior of Rule Of Thumb of the agents. The results showed for the first chapter that the implications of the consumption habit model with the discount stochastic factor that follows the premise of Brownian motion in the prices of financial assets was the one that best answered the hypotheses related to the proposed modeling, in the second article the estimated parameters signaled the existence of Rule of Thumb behavior in the decisions of consumption by the agents of the American economy, in addition to other evidences about its behavior, given the use of a portfolios of common factors.